Fast healing of ionic bonds in tough hydrogels under an acoustic excitation - Lee, Hyun-Hee; Kim, Yong-Woo; Woo, Jaesung; Park, Haedong; Hur, Kahyun; Suo, Zhigang; Sun, Jeong-Yun (ELSEVIER, 2019)
A hydrogel of covalently crosslinked chains and ionically crosslinked chains has exhibited high toughness. Under deformation, the covalently crosslinked network remains intact, and the ionically crosslinked network dissipates energy by breaking the ionic bonds. Because the broken ionic bonds can reform spontaneously, the damaged hydrogel can recover its initial state. However, the healing process of dissociated ionic bonds is slow. This paper shows that the healing process of dissociated ionic bonds accelerates under ultrasound radiation. Ultrasound enhanced the mobility of the dissociated chains, resulting in fast recovery of the mechanical properties. While a damaged gel thermally recovered 5 % of its energy density at room temperature in an hour, 37 % of the energy density was recovered using ultrasound in the same period. Molecular dynamic simulations were also included in this study to reveal the effect of ultrasound. (C) 2019 The Authors. Published by Elsevier Ltd.
Keywords: MOLECULAR-DYNAMICS; SONICATION